Évaluer le contenu des notifications d’alerte diffusées en France via FR-Alert® : enjeux scientifiques et retombées opérationnelles - Johnny Douvinet; Miangaly Rakoto; Delphine Grancher; Eric Daudé; Romain Moutard (Netcom)
In France, since June 2022, the prefectural authorities are capable to send a cell-broadcasted notification on mobile phones to all people located in a danger zone, using the platform so-called FR-Alert®. While numerous studies have demonstrated that this notification must be clear, precise and formulated with simple words, to be understood by the greatest number of people, no study has ever been carried out to evaluate the content of the notifications and to compare them with the state of the art. To fill this gap, a grid has been applied to notifications sent during drills (n=100) or real alerts (n=29), collected between May 2022 and February 2024. This allowed to calculate the frequency of the elements present and to valuate an overall score. The main results show that most of the messages followed the state of the art (73% of messages scored above average); some messages deviated significantly from the normative framework and were therefore problematic; the omitted elements are related to the timing and an internet link required to authenticate the alert sender; the increase in the number of exercises for several prefectures and over time have no effect on the score, which raises the question of the transfer of knowledge towards operational staff and the possibility of improving the platform.